Phosphors : synthesis and applications - Dhoble, Sanjay J.; Raju, B. Deva Prasad; Singh, Vijay (Singapore : Pan Stanford Publishing, 2018)
"Rare earthdoped luminescent materials play an integral role in modern life because of their tremendous applications ranging from scintillators, color displays, fluorescent lamps, and intensifying screens to dosimetry of ionizing radiations. Written and edited by prominent luminescence researchers, this book details cutting-edge research on luminescence materials and is illustrated throughout with excellent figures and references. It will appeal to anyone involved in luminescence research and its applications, especially advanced undergraduate-, graduate-, and postgraduate-level students of spectroscopy, solid state physics, luminescence, material synthesis, and optical properties and researchers working on the synthesis of optical materials, the characterization of luminescence materials, solid state lighting, radiation dosimetry luminescence, and phosphor applications."--Provided by publisher.
chapter 1 Hydrodynamic Aspects on Sonoluminescence / t
Includes bibliographic references and index.
Keywords: Optical materials; Optoelectronics; Phosphors